Predictors of Quality of Life in Adults with Epilepsy: A Systematic Review Comparing Studies from High-and Low/Middle-Income Countries - Mlandu, Nwabisa (Department of Psychology, 2024)
Epilepsy is the most prevalent of the non-communicable diseases that have a neurological origin. Of the approximately 50 million people worldwide who are affected, more than 80% of cases are found in low- and middle-income countries (LMICs) such as South Africa. Diminished quality of life (QoL) is common in people with epilepsy (PWE). Broadly speaking, QoL is defined as one's general wellbeing as perceived through subjective experiences and position in life. Several individual factors affect how PWE perceive their general wellbeing; these factors, which include the person's sociodemographic profile, epilepsy-related clinical characteristics, psychiatric comorbidities, and other psychosocial influences, therefore play important roles in determining their QoL. The current study aimed to undertake a systematic review that provided an updated integration and evaluation of knowledge on the predictors of QoL in adults with epilepsy. The review also aimed to describe how the influence of these predictors might differ in LMICs as compared to highincome countries (HICs). A total of 100 original research articles met the inclusion criteria for the systematic review (43 from HIC and 57 from LMICs). The results of the study showed that globally and specifically in HICs, an interaction of seizure-related factors and psychiatric comorbidities were the main predictors of QoL. In LMICs, however, the influence of sociodemographic factors was also profoundly significant, particularly level of education. Given that the burden of epilepsy is more profound in LMICs than in HICs, it is thus crucial that clinicians and researchers are aware of how the influence of these predictors might differ from one geographic region to another – such awareness will allow the design or adjustment of interventions to optimize them for use in different countries.